Flexible Pyrene/Phenanthro[9, 10‐d]imidazole‐Based Memristive Devices for Mimicking Synaptic Plasticity. (8th May 2019) - Ren, Yi; Chang, Chih-Li; Ting, Li-Yu; Zhou, Li; Mao, Jing-Yu; Zhang, Shi-Rui; Chou, Ho-Hsiu; Yang, Jia-Qin; Zhou, Ye; Han, Su-Ting
Abstract : Emulation of memory and learning functionalities of biological synapses using a two‐terminal electronic device with bidirectional progressive conductance modulation is an indispensable move toward the development of bio‐inspired neuromorphic networks. Herein, a small molecule 1‐phenyl‐2‐(4‐(pyren‐1‐yl)phenyl)‐1 H ‐phenanthro[9, 10‐ d ]imidazole (pPPI) is synthesized, and an organic synaptic device is investigated with bipolar resistive switching characteristics and bidirectional gradual conductance regulation for the first time. A facile solution‐processing approach can be used to deposit a uniform active layer on flexible substrates. Our pPPI‐based nonvolatile memory presents a superior electrical performance, such as relatively stable and reproducible bipolar resistive switching phenomena and a robust data retention capability. In particular, our device displays a remarkably large switching window of around 7.0 × 10 7, which is a record ON/OFF ratio compared with other small molecule‐based memories up to now. In addition, comprehensive cognitive functions of chemical synapses, for example, the excitatory postsynaptic current (EPSC), paired‐pulse facilitation/depression (PPF/PPD), spike‐rate‐dependent plasticity (SRDP), and spike‐time‐dependent plasticity (STDP) are successfully achieved. Our achievement of a synaptic device based on small molecules may boost the development of bio‐inspired neuromorphic systems using organic electronics. Abstract : A novel organic small molecule 1‐phenyl‐2‐(4‐(pyren‐1‐yl)phenyl)‐1 H ‐phenanthro[9, 10‐ d ]imidazole (pPPI) is synthesized, and an artificial organic synaptic device with pPPI as an active layer is investigated with bipolar resistive switching characteristics and bidirectional gradual conductance regulation. Bio‐inspired synaptic phenomena, including excitatory postsynaptic current, paired‐pulse facilitation, paired‐pulse depression, spike‐rate‐dependent plasticity, and spike‐time‐dependent plasticity, are implemented in the synaptic device.